Measuring pregnancy care: towards better maternal and child health - Sinni, Suzanne V. (Aust N Z J Obstet Gynaecol, 2016)
BACKGROUND: Obstetrics remains the largest medico‐legal liability in healthcare. Neither an increasing awareness of patient safety nor a long tradition of reporting obstetric outcomes have reduced either rates of medical error or obstetric litigation. International debate continues about the best approaches to measuring and improving patient safety. In this study, we set out to assess the feasibility and utility of measuring the process of maternity care provision rather than care outcomes. AIMS: To report the development, application and results of a tool designed to measure the process of maternity care. MATERIALS AND METHODS: A dedicated audit tool was developed, informed by local, national and international standards guiding best practice and then applied to a convenience sample of individual healthcare records as proof of function. Omissions of care were rated in order of severity (low, medium or high) based on the likelihood of serious consequences on patient safety and outcome. RESULTS: The rate of high severity omissions of care was less that 2%. However, overall rates of all omissions varied from 0 to 99%, highlighting key areas for clinical practice improvement. CONCLUSIONS: Measuring process of care provision, rather than pregnancy outcomes, is feasible and insightful, effectively identifying gaps in care provision and affording opportunities for targeted care improvement. This approach to improving patient safety, and potentially reducing litigation burden, promises to be a useful adjunct to the measurement of outcomes.